Алгоритмы распознавания строк в системах обнаружения вторжений на плис - Давиденко, А.Н.; Гильгурт, С.Я. (Моделювання та інформаційні технології, 2010)
The most known pattern-matching algorithms used in FPGA-based Network Intrusion Detection Systems are investigated. Their merits and disadvantages are exposed.